2021
DOI: 10.1186/s12917-021-02830-z
|View full text |Cite
|
Sign up to set email alerts
|

Cystic echinococcosis: an emerging zoonosis in southern regions of Khyber Pakhtunkhwa, Pakistan

Abstract: Background Cystic echinococcosis (CE) is one of the principal causes of economic loss to the livestock industry because of its morbidity and mortality of food-producing animals and condemnation of important visceral organs. Pakistan being an agricultural country having an extensive livestock sector, is mostly practiced by poor people, which has a fundamental role in the economy. The present study was aimed to conduct a cross-sectional survey and PCR based confirmation of Echinococcus granulosus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Post-mortem inspection of the internal organs in the slaughterhouses showed that the lungs and the liver were highly infected and more susceptible to echinococcosis. These findings were also demonstrated by Joanny et al (27), Khan et al (28), El-Dakhly et al (29) and Kere et al (30). The presence of a high number of cysts in the lungs and the liver may be due to specific intensive blood supply from the portal veins and hepatic arteries of the liver and soft consistency of the lung tissue that allows easy development of the cyst (10).…”
Section: Discussionsupporting
confidence: 53%
“…Post-mortem inspection of the internal organs in the slaughterhouses showed that the lungs and the liver were highly infected and more susceptible to echinococcosis. These findings were also demonstrated by Joanny et al (27), Khan et al (28), El-Dakhly et al (29) and Kere et al (30). The presence of a high number of cysts in the lungs and the liver may be due to specific intensive blood supply from the portal veins and hepatic arteries of the liver and soft consistency of the lung tissue that allows easy development of the cyst (10).…”
Section: Discussionsupporting
confidence: 53%
“…The reported prevalence is quietly high in different regions of Punjab such as 31.05 ( 39 ), 33.0, ( 30 , 31 ), 60.6 ( 40 ), 35.0 ( 12 ), and 6.67% ( 15 ). However, in Khyber Pakhtunkhwa province the reported prevalence was 14.57 ( 9 ) and 9.0% ( 25 ) in slaughtered animals. The prevalence of 17.0% was recorded in the current study in livestock population of the Malakand division.…”
Section: Discussionmentioning
confidence: 94%
“…Cystic echinococcosis is a parasitic infection with a worldwide distribution, producing substantial health and monetary losses ( 29 ). CE has been merely reported in Pakistani slaughtered animals, and only a few reports are available ( 9 , 12 , 14 , 15 , 17 , 25 , 30 – 33 ). The reported prevalence in slaughtered animals from India, Italy, Ethiopia, China, and Iran was 0.58 ( 34 ), 10.6 ( 35 ), 31.4 ( 36 ), 11.84 ( 37 ), and 10.7% ( 38 ), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cystic echinococcosis (CE) is a parasitic zoonotic disease with a worldwide distribution, particularly in developing countries ( 1 4 ). This disease is caused by a tapeworm of the species Echinococcus granulosus (EG) complex that has several distinct genotypes ( 5 ).…”
Section: Introductionmentioning
confidence: 99%